Empowering Migrants: Impacts of a Migrant's Amnesty on Crime Reports - Ana Maria Ibanez; Sandra V. Rozo; Dany Bahar (Institute of Labor Economics (IZA), 2020)
How can the regularization of approximately half a million migrant's impact crime reports in hosting areas? To identify the effects of this large amnesty, we match confidential administrative data on the location of undocumented migrants with department-monthly data from crime reports and compare crime outcomes in departments that were granted different average time windows to register for the amnesty online, before and after the amnesty roll-out. We document that the regularization caused a reduction of domestic crime and an increment on sexual crime reports. Both results are in line with qualitative evidence suggesting that the regularization empowered migrants to report crimes against them and also improved their mental health.
Keywords: D72; F2; O15; R23; 330; migration; crime; regularization